The man with the iron fists 2 [videorecording (DVD)] - Reiné, Roel; RZA (Rapper); RZA (Rapper); Nguyen, Dustin, 1962-; Tagawa, Cary-Hiroyuki (Universal Studios Home Entertainment, 2015)
A reluctant villager joins forces with a mysterious outsider to fight off powerful evil forces, both earthly and otherworldly, in a 19th century Chinese mining town. When a stranger, Thaddeus, is found badly wounded near the village, miner Li Kung and his wife Ah Ni offer him refuge. As he heals, he becomes entrenched in a conflict that pits the townsfolk against the evil Master Ho, his nefarious Beetle Clan and the terrifying Lord Pi.--Container.